A Web-based Decision Support Tool for Timing Fungicide Applications in Strawberry - Willingthon Pavan; Clyde W. Fraisse; Natalia A. Peres (EDIS)
AE450, a 5-page illustrated fact sheet by Willingthon Pavan, Clyde W. Fraisse, and Natália A. Peres, describes a web-based tool for timing fungicide applications in strawberries that can reduce the number of sprays and cost of production, especially in years when the conditions for disease are not favorable. Includes references. Published by the UF Department of Agricultural and Biological Engineering, August 2009.